2016
DOI: 10.1111/acps.12554
|View full text |Cite
|
Sign up to set email alerts
|

Geographical disparities in prescription practices of lithium and clozapine: a community‐based study

Abstract: A sufficient density of GPs and an effective communication and collaboration between mental healthcare services and primary care seems to favor greater access to psychotropic drugs with demonstrated efficacy but often viewed as 'risky' to prescribe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Nevertheless, adjunctive lithium was less frequently prescribed in our survey (4.11% of all participants) than for instance augmentation with antipsychotics (25.67% of all participants). Probably, the use of lithium in the clinical practice is limited by the need of continuous plasma level measurements to ensure the achievement of the therapeutic window and due to the anticipation of adverse effects . On the other hand, the increased risk for metabolic adverse effects and sedation should be critically taken into account when considering SGA augmentation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adjunctive lithium was less frequently prescribed in our survey (4.11% of all participants) than for instance augmentation with antipsychotics (25.67% of all participants). Probably, the use of lithium in the clinical practice is limited by the need of continuous plasma level measurements to ensure the achievement of the therapeutic window and due to the anticipation of adverse effects . On the other hand, the increased risk for metabolic adverse effects and sedation should be critically taken into account when considering SGA augmentation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine ADRs of interest showed a peak in 2008, but an overall increase was observed between 2010 and 2018. One could argue that this upward trend may have been associated with a range of factors, including the increasing rates of worldwide availability of clozapine due to an overwhelming evidence of its effectiveness [2,[49][50][51] and/or a major awareness of the relevant and significant impact of pharmacovigilance processes and issues, resulting in a rise of spontaneous reporting practices related to safety monitoring of medicinal products in general [52].…”
Section: Discussionmentioning
confidence: 99%
“…In a study in France, only 1.2% of the users of antipsychotics was using clozapine. However, 6.6% of the total population was using antipsychotics, so the clozapine prescription rate among patients with NAPD may be much higher ( 13 ). Although different study designs may contribute to these differences, a large international database study ( 25 ) also showed that prescription rates in the Netherlands are higher than in most other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of clozapine prescription rates show large international differences ( 13 15 ). In the Netherlands, the proportion of patients with Non-Affective Psychotic Disorder (NAPD) using this drug is unknown.…”
Section: Introductionmentioning
confidence: 99%